OPINIONS OF STUDENTS WHO STAY IN PRIVATE STUDENT RESIDENCES ABOUT ADMINISTRATIVE PROBLEMS (CASE STUDY OF ELAZIĞ) - Necmi GÖKYER (Fırat University, 2019)
This study aims to determine opinions of students who stay in private student residences about administrative problems. The study is made using descriptive scanning model and since 5 of the 16 student residences operating in Elazığ in 2011-2012 academic year did not permit questionnaire application, population of the study is composed of 1200 students staying in the remaining 11 student residences in Elazığ. Sample of the study is composed of 498 students chosen with simple random sampling method from among students staying in the said 11 residences. For collection of data, a questionnaire titled "opinions of students staying in private student residences about administrative problems" was used which was developed by the researcher. With the data obtained, arithmetic average, standard deviation, t test, one way analysis of variance were made. According to findings of the research 47.2% of the students find food prices high. Officers working in the residences are behaving towards students respectfully in general. Administrators are dealing with students very much at sometimes level. Sufficient education environment for studying according to student number can sometimes be found.